ANALISIS KESTABILAN LERENG DISPOSAL "X" PADA TAMBANG TERBUKA BATUBARA, KABUPATEN BALANGAN, KALIMANTAN SELATAN - Putri Anjani, Anissa; Radityo, Daniel (Jurnal Ilmiah Geologi PANGEA, 2025)
Coal mining activities involve waste material disposal, where slope stability must be maintained to ensure operational safety. This study aims to analyze the slope conditions and determine the factor of safety (FoS) of the disposal slope design to ensure compliance with the minimum safety criteria. The study area is located within the Mining Business Permit (IUP) of PT “Y”, Balangan Regency, South Kalimantan Province. The analysis was conducted using the Limit Equilibrium Method (LEM) with the Morgenstern–Price approach and Mohr–Coulomb failure criterion, utilizing Slide 6.0 software. The data used include actual and 2025 design topography, Standard Penetration Test (SPT) borehole data, geotechnical parameters (cohesion, internal friction angle, and unit weight), and groundwater levels obtained from standpipe piezometers. The results show that all ten analyzed disposal slope sections have FoS values greater than 1.3, indicating that the slopes are stable and suitable for further development.